Analgesic efficacy of ultrasound‐guided transversus abdominis plane block after cesarean delivery: A systematic review and meta‐analysis. Issue 9 (15th June 2021) - Wang, Peng; Chen, Xu; Chang, Ying; Wang, Yanping; Cui, Hongyan
Abstract: Purpose: The meta‐analysis is aimed to further access the analgesic efficacy of ultrasound‐guided transversus abdominis plane (USG‐TAP) block after cesarean section (CS). Methods: Electronic databases were searched for eligible studies. Primary objectives were pain‐related outcomes. Weighted mean differences (WMDs) or standardized mean differences (SMDs), as well as risk ratios (RRs) with 95% confidence intervals (CIs), were used to calculate estimates. Subgroup analyses were done based on whether USG‐TAP blocks were performed with long‐acting intrathecal opioids (ITO). Results: A total of 17 studies were included. When compared with control groups (placebo or no blocks), USG‐TAP block resulted in lower cumulative opioid consumption at 6 h (WMD: −8.32; 95% CI: −14.86, −1.79), 12 h (WMD: −10.75; 95% CI: −20.93, −0.57), and 24 h (WMD: −12.71, 95% CI: −21.28, −4.14). No significant differences were demonstrated among dynamic or resting pain scores. Patients in USG‐TAP groups needed longer time to request first analgesic (WMD: 3.56; 95% CI: 1.43, 5.68) and showed a lower requirement of opioid rescue analgesia for breakthrough severe pain during 24 h (RR: 0.40; 95% CI: 0.18, 0.86). Subgroup analyses showed USG‐TAP blocks did not afford additional benefit in the presence of intrathecal morphine. Also, reduced need for antiemetics after CS and higher maternal satisfaction were provided by USG‐TAP blocks. Conclusion: USG‐TAP block can provide significantly effective analgesia for patients who underwent CS in the absence of long‐acting ITO and therefore are worth promoting in the setting of long‐acting ITO being unfeasible.